An integrated mental health video consultations model for patients with somatic symptom disorder in primary care: the randomized VISION pilot trial - Haun, Markus W.; Eickels, Deborah van; Tönnies, Justus; Graue, Leike; Ayoub-Schreifeldt, Marayah; Wensing, Michel; Hartmann, Mechthild; Szecsenyi, Joachim; Wild, Beate; Friederich, Hans-Christoph (Journal of psychosomatic research, 2024)
Objective - Symptoms of somatic symptom disorder (SSD) are one of the most common reasons for consultations in primary care. However, specialized psychological services are mostly unavailable. This pilot trial aimed to determine the feasibility, acceptability, and safety of the integrated mental health video consultations VISION model for patients with SSD in primary care. - Methods - We conducted a parallel group, randomized controlled pilot trial involving fifty-one patients with SSD from ten primary care practices in Germany, who we randomized to the VISION model or enhanced treatment-as-usual (eTAU). The VISION model comprised five video consultations which featured diagnostic clarification, psychoeducation (acknowledging and legitimizing of symptoms), and brief psychological therapy. eTAU included training primary care practice teams on the DSM-5 concept of SSD and on current guideline recommendations for its treatment in primary care. We assessed feasibility as the primary outcome at 6-months, measuring efficiency of recruitment, intervention acceptability, and safety. - Results - Recruitment was efficient reflected in an overall recruitment yield (number randomized per number screened) of 55% (51/92) and a consent rate (number randomized per number eligible) of 94% (51/54). Acceptability of the intervention was high with 98% (123/125) of the video consultations conducted as planned. No serious adverse events were reported in either group. - Conclusion - An integrated mental health video consultations VISION model for patients with SSD presenting to primary care is feasible, acceptable, and safe. Potential clinical effectiveness of the model should be evaluated in confirmatory trial implementing the multifaceted approach tailored to the individual patient with SSD directly into primary care practice. - Trial registration - The trial protocol was registered at German Clinical Trials Register (number: DRKS00026075, https://www.drks.de).
Online verfügbar: 14. Mai 2024, Artikelversion: 17. Mai 2024
Gesehen am 18.09.2024